Keragaman Gender di Dewan Komisaris dan Risiko Perusahaan: Perspektif Teori Agensi Perilaku - Medidjati, R Adam; Nugraha, Nugraha; Heryana, Toni; Hartono, Pierdijono (Universitas Pendidikan Indonesia, 2023)
The purpose of this study is to verify the influence of gender diversity in the Board of Commissioners on the financial risks of the company from the perspective of behavioral agency theory, where the presence of gender diversity in the board of commissioners can improve the ability of the board of commissioners to manage company risks. However, there is also the possibility that gender diversity on the board of commissioners may increase the company's risk. This can happen if there is a conflict between members of the board of commissioners of different genders, thereby disrupting the smooth decision-making process. The company's financial risk indicators measured in this study are Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR). This research study was conducted on companies incorporated in LQ45 with a research period from 2015 to 2020 as many as 51 companies. This study was conducted using secondary data and the data was processed using unbalanced panel data regression with the help of the EVIEWS 12 application. The results of this study show that gender diversity in the Board of Commissioners has a significant effect on DAR where an increase in the composition of the number of men will reduce DAR by -0.53 this means that gender diversity will increase the company's risk in DAR indicators. But on the contrary, this gender diversity does not have a significant effect on DER.